STUDI EVALUASI PROSES PELAYANAN PRIMA PERIJINAN TERPADU SATU PINTU di BPPT KOTA SEMARANG - Putri Widayanti; Purwoko .; Lusia Astrika (Journal of Politic and Government Studies, 2014)
In the conduct of public services to the society, the most important thing that was supposed to take precedence in society is satisfaction in getting the service. Provision of public services in accordance with the standards of the public service is the process of excellent service to the community. Excellent service is the best service is given with emphasis on simplicity, speed, timeliness and compliance with the applicable standards to create a satisfaction to the public. The problems discussed in this research include efforts made in achieving excellent service and the factors restricting anything encountered in achieving the award of excellent service to the community at the service of the integrated permitting agency (BPPT) of Semarang City.This study uses qualitative research methods of evaluation. The focus of the study include: (1) efforts in realizing BPPT excellent service to the community, (2) inhibiting factors encountered in achieving BPPT providing excellent service to the community.Based on the results of the qualitative evaluation of the obtained research results and discussion that shows that efforts in the matter of permitting excellent service at BPPT of Semarang City there are still some obstacles. A variety of factors restricting that needs to be fixed, that is existence of the technical team was still in the service of the other departments concerned, the uncertainty of the time of the completion of permitting, infrastructure and facilities, the existence of scalpers who made the cost of licensing to be doubled, the processing of the file permission must still be out to departments related as well as incomplete files from the applicants.The process of excellent service is still far from what is expected by society. BPPT of Semarang City should have been stricter in doing the superintendence toward the scalper and get full pander in publishing of permitting so that giving services become more effective and efficient.